Synthesis and characterization of O-Carboxymethylchitosan as an alternative to the use of Hyaluronic Acid (Research, Society and Development, 2022)
Hyaluronic acid (HA) has been an important component in several fields, such as dermal filling, tissue engineering, treatment of the vascular and cartilaginous region, and its application is limited because its excessive use can promote a reduction in cell adhesion, due to its presence of negative charges, characteristic of this material. To solve this limitation, a cationic and anionic material can be used, such as O-Carboxymethylchitosan (O-CMQ), which has a similar chemical structure and similar properties to HA. Therefore, this work aimed to determine the conditions for the synthesis and characterization of O-Carboxymethylchitosan (O-CMQ), and to evaluate its application as an alternative to hyaluronic acid. From the chitosan produced and characterized, the synthesis of O-CMQ was carried out in the proportions 1:1, 1:2 and 1.5:2 (m/v), followed by the characterizations through Visual Analysis, Optical Microscopy (OM), Fourier Transform Infrared Spectroscopy (FTIR), Hydrogen Potential (pH) and Conductivity, Thermogravimetry Analysis (TGA) and Differential Scanning Calorimetry (DSC). It was concluded that the synthesis methodology was efficient for the production of O-Carboxymethylchitosan with different properties. The comparison with hyaluronic acid confirmed the chemical, physical and biological similarities between the samples, being promising for application as a substitute for this material.